2003
DOI: 10.1021/jf020981u
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared Spectroscopy for Cost Effective Screening of Foliar Oil Characteristics in aMelaleuca cajuputiBreeding Population

Abstract: The identification of Melaleuca cajuputi leaf samples (trees) that demonstrate enhanced oil characteristics using near infrared (NIR) spectroscopy is described. Leaf samples from an unthinned M. cajuputi seedling seed orchard in Indonesia were collected and air-dried, and their 1,8-cineole content and oil concentrations were determined. NIR spectra of the leaves were obtained, and calibrations for 1,8-cineole content and oil concentration were developed using spectra that had been selected using spectral featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
10

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 6 publications
2
46
0
10
Order By: Relevance
“…According to Schimleck et al (2003), a RPD value higher than 1.5 is considered satisfactory for preliminary readings and predictions (screenings), and for tree selection in forest improvement programs.…”
Section: Calibration Of Mechanical Properties Of Woodmentioning
confidence: 99%
“…According to Schimleck et al (2003), a RPD value higher than 1.5 is considered satisfactory for preliminary readings and predictions (screenings), and for tree selection in forest improvement programs.…”
Section: Calibration Of Mechanical Properties Of Woodmentioning
confidence: 99%
“…The predictive ability of calibrations was assessed by calculating the ratio of performance to deviation (RPDJ (ratio of the standard deviation of the reference data to the SEP) (Williams and Sobering 1993). An RPD of greater than 2.5 is considered satisfactory for screening (Williams and Sobering 1993); however, it has been shown that calibrations with an RPD of approximately 1.5 can be useful for initial sample screening (Schimleck et al 2003).…”
Section: Calibration Developmentmentioning
confidence: 99%
“…Segundo Schimleck et al (2003), para utilizações no campo das ciências florestais, um RPD maior que 1,5 é considerado satisfatório para leituras e predições preliminares (screenings) e para seleção de árvores em programas de melhoramento.…”
Section: Análises Químicas Da Madeiraunclassified